An Investigation About 6th Grade Students' Attitudes Towards Mathematics. (13th May 2015) - Kibrislioglu, Nermin
Abstract: The purpose of this study is to investigate 6 th students' attitudes towards mathematics, the gender effect on attitude and the relationship between attitude and achievement. The data were collected from 120 6 th grade students. Participants were assigned to complete mathematics attitude scale which is developed by Aşkar (1986). In addition students were grouped as low, medium and high achiever with respect to their grades. Students' attitude scores were computed, descriptive statistics were examined and scores were compared with respect to achievement and gender. The results indicated that students have relatively positive attitudes towards mathematics. The difference between high and low achiever students' attitude scores is significant. Hence there is a relationship between attitude and achievement. On the other hand no gender difference was found in this study.